1966
DOI: 10.1037/h0023793
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of adrenaline and noradrenaline during prolonged perceptual deprivation.

Abstract: Ss who successfully completed a week of perceptual isolation showed no significant changes in urinary excretion of adrenaline and noradrenaline relative to a group of control Ss. They also showed no changes on a behavioral measure of subjective stress and mood. Isolation "quitters," i.e., those who failed to complete the prescribed period, also showed no change in noradrenaline. Their urinary excretion of adrenaline, however, increased, but only in Ss who terminated isolation late in the 1-wk period. Perhaps t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1968
1968
1980
1980

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…The results on the sss, comparing the stress scores obtained during the experiment with those obtained before, were not statistically significant, a finding which may be related to the presence, in the PD and SD groups, of some degree of pre-experimental apprehension about entering the isolation chamber. Such an apprehension effect has been observed previously not only in isolation studies (e.g., Zubek & Schutte, 1966) but also in other types of stressful conditions (e.g., Elmadjian, Hope, & Lamson, 1957;Goodall & Berman, 1960). However, a comparison involving the post-experimental period indicated that both the PD and SD groups showed a significantly greater degree of stress than did the controls; the PD-SD difference was not significant.…”
Section: Discussionsupporting
confidence: 67%
“…The results on the sss, comparing the stress scores obtained during the experiment with those obtained before, were not statistically significant, a finding which may be related to the presence, in the PD and SD groups, of some degree of pre-experimental apprehension about entering the isolation chamber. Such an apprehension effect has been observed previously not only in isolation studies (e.g., Zubek & Schutte, 1966) but also in other types of stressful conditions (e.g., Elmadjian, Hope, & Lamson, 1957;Goodall & Berman, 1960). However, a comparison involving the post-experimental period indicated that both the PD and SD groups showed a significantly greater degree of stress than did the controls; the PD-SD difference was not significant.…”
Section: Discussionsupporting
confidence: 67%
“…The "privacy" theory certainly merits more attention because some clinicians feel that certain inmates (those who have some schizo-affective symptoms) seek solitary confinement only in order to reinforce their psychopathology . Zubek and Schutte (1966) and Zubek et d. (1969) have reported that those who quit isolation have significantly lower baseline adrenaline levels than Ss who successfully completed sensory deprivation. Haythom (1967) reported that quitters had lower adrenaline and higher uric acid levels than Ss who were able to endure isolation.…”
Section: Discussionmentioning
confidence: 98%
“…Zubek (1969) has found that most of his college Ss who quit sensory deprivation have done so on the second or third day. Zubek and Schutte (1966) inferred that quitters may be biochemically or "constitutionally" different. From a medical and psychiatric viewpoint, this suggestion merits further study with those inmates who cannot cope with confinement.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the early quitters, however, these affective changes were not accompanied by an increased catecholamine excretion, a disparity often noted in other studies relating biochemical and behavioral measures of stress. A comparison of the results of this immobilization study with those derived from an earlier study of perceptual isloation (Zubek & Schutte, 1966), both involving a 1-wk. duration, indicates that these two conditions produce essentially similar biochemical and affective changes.…”
Section: Successful Invnobihzolwn Ss •-• «• 16mentioning
confidence: 88%
“…of perceptual isolation. Zubek and Schutte (1966) recently reported that Ss who successfully endured a week of perceptual isolation showed no significant changes in subjective stress and mood or in the urinary excretion of adrenaline and noradrenaline (catecholamines) relative to a group of recumbent controls. On the other hand, the isolation quitters showed an increase in adrenaline, but only in Ss who terminated the experiment late in the 1-wk.…”
Section: University Of Manitobamentioning
confidence: 99%